Central Queensland University's Course Management Systems: Accelerator or brake in engaging change? - McConachie, Jeanne; Danaher, Patrick Alan; Luck, Jo; Jones, David (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
Central Queensland University (CQU) is a highly complex institution, combining campuses in Central Queensland and distance education programs for Australian domestic students with Australian metropolitan sites for international students and a number of overseas centres, also for international students. In common with many other universities, CQU has recently reviewed its course management systems (CMSs). In doing so, CQU has signalled its desired strategic position in managing its online learning provision for the foreseeable future.This paper analyzes that strategic position from the perspective of the effectiveness of CQU’s engagement with current drivers of change. Drawing on online survey results, the authors deploy Introna’s (1996) distinction between teleological and ateleological systems to interrogate CQU’s current position on CMSs – one of its most significant enterprises – for what it reveals about whether and how CQU’s CMSs should be considered an accelerator of, or a brake on, its effective engagement with those drivers of change. The authors contend that a more thorough adoption of an ateological systems approach is likely to enhance the CMS’s status as an accelerator in engaging with such drivers.